Phenylethenyl‐Substituted Triphenylamines: Efficient, Easily Obtainable, and Inexpensive Hole‐Transporting Materials. Issue 44 (17th September 2013) - Malinauskas, Tadas; Daskeviciene, Maryte; Bubniene, Giedre; Petrikyte, Ieva; Raisys, Steponas; Kazlauskas, Karolis; Gaidelis, Valentas; Jankauskas, Vygintas; Maldzius, Robertas; Jursenas, Saulius; Getautis, Vytautas
Abstract Star‐shaped charge‐transporting materials with a triphenylamine (TPA) core and various phenylethenyl side arm(s) were obtained in a one‐step synthetic procedure from commercially available and relatively inexpensive starting materials. Crystallinity, glass‐transition temperature, size of the π‐conjugated system, energy levels, and the way molecules pack in the solid state can be significantly influenced by variation of the structure of these side arm(s). An increase in the number of phenylethenyl side arms was found to hinder intramolecular motions of the TPA core, and thereby provide significant enhancement of the fluorescence quantum yield of the TPA derivatives in solution. On the other hand, a larger number of side arms facilitated exciton migration through the dense side‐arm network formed in the solid state and, thus, considerably reduces fluorescence efficiency by migration‐assisted nonradiative relaxation. This dense network enables charges to move more rapidly through the hole‐transport material layer, which results in very good charge drift mobility (μ up to 0.017 cm2 V −1 s−1).